2018
DOI: 10.1371/journal.pone.0198964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of community-based intervention on knowledge, attitude, and self-efficacy toward home injuries among Egyptian rural mothers having preschool children

Abstract: BackgroundParent’s level of knowledge, state of their attitude, and their self-efficacy are the most incriminated reasons for the faulty application of the first aid measures, particularly in children's home injuries.ObjectivesTo assess the effect of a health education intervention on improving knowledge, attitude and self- efficacy of mothers having preschool children about home injuries and the basic first aid measures.MethodsA pre-posttest evaluation of the effect of a health education intervention on chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 12 publications
3
14
0
3
Order By: Relevance
“…A similar study that also involves a one-day education event in Egypt to educate mothers on possible home injuries in preschool children was able to show an increase to 18.90 from 10.21 in the total score. 19 In conclusion, knowledge regarding basic knowledge of burn, first aid in burns, and nutrition in burns has improved significantly after a one-day health promotion, showing the effectiveness of this type of approach. It is then suggested that this type of program should be performed and researched more often by involving a larger population sample, especially in areas prone to fire in Indonesia, in order to provide better care and improve the recovery rate of burn patients.…”
Section: Discussionmentioning
confidence: 89%
“…A similar study that also involves a one-day education event in Egypt to educate mothers on possible home injuries in preschool children was able to show an increase to 18.90 from 10.21 in the total score. 19 In conclusion, knowledge regarding basic knowledge of burn, first aid in burns, and nutrition in burns has improved significantly after a one-day health promotion, showing the effectiveness of this type of approach. It is then suggested that this type of program should be performed and researched more often by involving a larger population sample, especially in areas prone to fire in Indonesia, in order to provide better care and improve the recovery rate of burn patients.…”
Section: Discussionmentioning
confidence: 89%
“…In our study, majority (74.8%) of the mothers were housewives which is comparable to other similar studies in which majority of mothers were housewives. [ 6 10 11 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…After taking consent, participant mothers were asked to complete a semi-structured, self-administered questionnaire that was adapted from a validated and reliable instrument. [ 6 ] The knowledge questions were reviewed and modified according to Guidelines from the American Heart Association and American Red Cross and American paediatric association. [ 7 8 ] The data were collected during February to June 2020.…”
Section: Methodsmentioning
confidence: 99%
“…10 Another similar study was conducted in Egypt to educate mothers about possible home injuries in preschool children and was able to show an increase to 18.90 from 10.21 in the total score. 19 Prevention in developing countries is absolutely different from that of developed countries, where burn prevention has been integrated to their education and community systems. 12 However, it should be the goal of the developing countries for conducting continuous education on burn prevention as good knowledge will lead to good practice that will significantly reduce burnrelated disfigurement, disability, and death.…”
Section: Discussionmentioning
confidence: 99%